2018
DOI: 10.15252/embr.201745401
|View full text |Cite
|
Sign up to set email alerts
|

Restoration of 5‐hydroxymethylcytosine by ascorbate blocks kidney tumour growth

Abstract: Loss of 5-hydroxymethylcytosine (5hmC) occurs frequently in a wide variety of tumours, including clear-cell renal cell carcinoma (ccRCC). It remains unknown, however, whether the restoration of 5hmC patterns in tumours could have therapeutic efficacy. Here, we used sodium L-ascorbate (vitamin C, AsANa) and the oxidation-resistant form L-ascorbic acid 2-phosphate sesquimagnesium (APM) for the restoration of 5hmC patterns in ccRCC cells. At physiological concentrations, both show anti-tumour efficacy during long… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 41 publications
1
40
0
Order By: Relevance
“…Considering that 5mC and TET2 are both closely related to the regulation of DNA methylation, it might be reasonable to hypothesize that 5mC and TET2 also participate in the etiology of the existence or progression of precancerous lesion. In this study, we found that 5hmC and TET2 expressions were both negatively correlated with the histological classification, and here were several possible explanations to the results in our study: (a) 5hmC and TET2 might prevent the formation or repress the progression of breast precancerous lesion via modulating stemness or other related processes, which still need more in vivo and in vitro experiments to validate; (b) 5hmC and TET2 might also inhibit precancerous lesion development and progression via similar mechanism by which they suppress the cancer progression, for instance, repressing malignant behaviors of cancer cells by mediating multiple oncogenic signaling pathways . However, we did not find a statistically significant correlation between 5mC and histopathological classification, which may be due to the dual role of 5mC in cancer pathogenesis found in other cancers, or a relatively small sample size …”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…Considering that 5mC and TET2 are both closely related to the regulation of DNA methylation, it might be reasonable to hypothesize that 5mC and TET2 also participate in the etiology of the existence or progression of precancerous lesion. In this study, we found that 5hmC and TET2 expressions were both negatively correlated with the histological classification, and here were several possible explanations to the results in our study: (a) 5hmC and TET2 might prevent the formation or repress the progression of breast precancerous lesion via modulating stemness or other related processes, which still need more in vivo and in vitro experiments to validate; (b) 5hmC and TET2 might also inhibit precancerous lesion development and progression via similar mechanism by which they suppress the cancer progression, for instance, repressing malignant behaviors of cancer cells by mediating multiple oncogenic signaling pathways . However, we did not find a statistically significant correlation between 5mC and histopathological classification, which may be due to the dual role of 5mC in cancer pathogenesis found in other cancers, or a relatively small sample size …”
Section: Discussionmentioning
confidence: 51%
“…As for 5hmC, a previous study reveals that epigenetically reduction of TET3 expression decreases the 5hmC expression in both tumor tissue and cancer cells, and this process subsequently advocates the tumor progression of glioblastoma in vitro . And another study illustrates that restoring the 5hmC using ascorbate represses the tumor growth of clear‐cell renal cell carcinoma in vitro . And a previous study elucidates that decline of 5hmC level in tumor tissue correlates with the existence of papillary thyroid carcinoma (PTC) and malignant behavior of PTC in vitro .…”
Section: Discussionmentioning
confidence: 99%
“…The down-regulated expression of IDH1 in kidney cancer contributes to the global loss of 5hmC in RCC (28). Consistently, ectopic expression of IDH1 and pharmacologically increasing intracellular 2-KG can restore the global levels of 5hmC, and consequently, can inhibit tumor growth (28,35).…”
Section: The Function Of Dna Demethylation In Kidney Cancermentioning
confidence: 85%
“…AA antitumoral effect is not only restricted to the promotion of ROS. Ge et al (2018) suggests that vitamin C analogs may play a role in cell reprogramming and growth regulation by enhancing the catalytic activity of ten-eleven translocation (TET) enzymes responsible for the oxidation of 5-methylcytosine (5 mC) a wellknown differentiation promoting agent. Loss of 5 mC expression correlates with the development of several aggressive form of cancer.…”
Section: Effect Of Pharmacologic Vitamin C In Cancer Cellsmentioning
confidence: 99%
“…Loss of 5 mC expression correlates with the development of several aggressive form of cancer. Therefore, AA dependent restoration underlines the role of AA and its analogs in cancer epigenetics, inducing an alteration in the differentiation potential of cancer stem cells, playing a role avoiding cancer metastasis (Ge et al, 2018;Satheesh et al, 2020).…”
Section: Effect Of Pharmacologic Vitamin C In Cancer Cellsmentioning
confidence: 99%